Mushroom Poisoning in the Northeast of Iran; a Retrospective 6-Year Epidemiologic Study - Dadpour, Bita; Tajoddini, Shahrad; Rajabi, Maliheh; Afshari, Reza (Archives of Academic Emergency Medicine, 2017)
Introduction: Toxic mushrooms are distributed across the globe with over 5000 species. Among them, 100 species are responsible for most of the cases of mushroom poisoning. This study aimed to evaluate the epidemiologic pattern of mushroom poisoning among patients referred to the main toxicology center of Mashhad province located in North-east of Iran. Method: This cross-sectional study was conducted on patients with final diagnosis of mushroom poisoning referred to the toxicology center of Mashhad, Iran, from February 2005 to 2011. Patients’ demographic characteristics, clinical presentations, laboratory findings, outcomes, and therapeutic measures were collected using a predesigned checklist and searching patient’s profile. Results: 32 cases with the mean age of 24.6 ± 16.7 years were presented to the toxicology center following mushroom poisoning (59% female). Mushroom poisoning accounted for 0.1% of all admitted cases. The mean time elapsed from consumption to referral to poisoning department was 61.9 ± 49.4 hours. 19 (59%) cases were discharged with complete recovery, 7 (22%) expired, and 6 (19%) cases left hospital against medical advice. Mushroom poisoning mortality accounted for 1.5% of deceased cases in the studied center. There was significant relationship between mortality rate and higher values of INR (p = 0.035), PT (p = 0.011) and PTT (p = 0.003). Likewise, there was significant relationship between the need for mechanical ventilation and higher values of INR (p = 0.035), PT (p = 0.006) and PTT (p = 0.014). The relationships between the need for ICU admission, mechanical ventilation, and mortality rate with the rise of hepatic transaminases and serum bilirubin were not significant. Conclusion: Based on the findings, the prevalence of mushroom poisoning among patients referred to Mashhad toxicology center was very low (0.1%), but with a high mortality rate of 22%. Nausea and vomiting were the most common early symptoms of intoxication and higher values of coagulation profile were correlated with poor outcome.